Assessing Drudgery Perceived by Agricultural Labourers in Chikkaballapur District of Karnataka - Ramanji, R. S.; Sarkar, A.; Mhatre, C. S.; Argade, S. D. (International Journal of Economic Plants, 2023)
The present study was conducted in Chikkaballapur district of Karnataka, India during 2019 to investigate amount of drudgery faced by agricultural labourers. Primary data collected for 13 selected farm operations from randomly selected 200 (144 men and 56 women) agricultural laborers using structured interview schedule for assessing drudgery perceived by them in performing these 13 operations. The results revealed that women labourers were perceived more drudgery in farm operations as compared men labourers. Women labourers perceived weeding, stubble collection and pesticide application were highest drudgery prone activities whereas men labourers perceived weeding, stubble collection and harvesting were highest drudgery prone activities. Out of thirteen selected farm activities, seed treatment was significantly lowest drudgery prone and weeding was the highest drudgery prone activity for both men and women labourers in the study area. Experience, family size and duration of employment were found to have significant and negative relationship with average drudgery and age & income were positively related with average drudgery. The drudgery among both men and women labourers can be reduced by gaining work experience, using ergonomically refined tools and proper management of employment pattern, duration and income.